2023
DOI: 10.3390/jrfm16010051
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bitcoin Price Prediction Using Machine Learning

Abstract: The research purpose of this paper is to obtain an algorithm model with high prediction accuracy for the price of Bitcoin on the next day through random forest regression and LSTM, and to explain which variables have influence on the price of Bitcoin. There is much prior literature on Bitcoin price prediction research, and the research methods mainly revolve around the ARMA model of time series and the LSTM algorithm of deep learning. Although it cannot be proved by the Diebold–Mariano test that the prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…When comparing the results of the PA with Chen (2023) , the PA achieves superior results in both root mean squared error (RMSE) and MAPE, as shown in Table 7 . The improvement in performance is attributed to the enhanced data collection, data analysis and processing, and model selection and hyperparameter tuning steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the results of the PA with Chen (2023) , the PA achieves superior results in both root mean squared error (RMSE) and MAPE, as shown in Table 7 . The improvement in performance is attributed to the enhanced data collection, data analysis and processing, and model selection and hyperparameter tuning steps.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that on-chain metrics are a good supplementary tool to existing deep learning techniques when it comes to cryptocurrency price prediction. Most recently, Chen (2023) developed a Bitcoin price prediction system using an RF model and 47 metrics, divided into eight categories: Bitcoin price variables, technical features of Bitcoin, other cryptocurrencies, commodities, market index, foreign exchange, public attention, and dummy variables of the week. The model was trained on two periods, one ranging from April 2015 to October 2018 and the other from October 2018 to April 2022.…”
Section: Introductionmentioning
confidence: 99%
“…The primary stream of research aims at discovering the dynamics of the cryptocurrency market and its potential influence on the global financial system (Dwyer, 2015; Hendrickson et al , 2016; Fama et al , 2019; Morillon, 2022; Shakri, 2022). Other popular sub-streams aim at predicting bitcoin price movements (Morillon and Chacon, 2022; Chen, 2023) and comprehending the volatility of bitcoin price returns (Aalborg et al , 2019; Miglietti et al , 2019; Kinateder and Papavassiliou, 2021; Sosa et al , 2022). Another widely explored sub-stream of research in the domain is examining netizens’ thoughts and expectations regarding bitcoin price returns (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An algorithm model combined random forest regression and LSTM was chosen to predict the price of Bitcoin by Junwei Chen [4].…”
Section: Popular Machine Learning Algorithms For Stock Price Predictionmentioning
confidence: 99%